2018
DOI: 10.3390/su11010051
|View full text |Cite
|
Sign up to set email alerts
|

Study on Factors Affecting the Agricultural Mechanization Level in China Based on Structural Equation Modeling

Abstract: The subsidy policy for the purchase of agricultural machinery and China's Agricultural Mechanization Promotion Law have been implemented since 1998 and 2004, respectively. The goal of the policy and the law is to improve the agricultural mechanization level (AML) in China. Policymakers expect that the AML could be increased by improving the agricultural equipment level (AEL). The AML in China is affected by many factors. However, only a few studies have investigated the effects of the AEL on the AML. To fill t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…The energy primarily used in different agricultural operations is listed in Table 4. Agricultural machinery and tractor use energy was estimated using following expression (Li et al, 2019)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy primarily used in different agricultural operations is listed in Table 4. Agricultural machinery and tractor use energy was estimated using following expression (Li et al, 2019)…”
Section: Methodsmentioning
confidence: 99%
“…is machine energy (MJ ha −1 ), G is the wight of machine (kg), is the production energy (MJ kg −1 ), T is the total life (h) and W is the effective field capacity (ha h −1 ). Diesel energy was measured by quantity of fuel consumed during crop production (Li et al, 2019). FC = Pm×R×SFC (6) Where FC is the fuel consumprion (l h −1 ), Pm is the tractor horsepower (kW), R is the loading ratio and SFC is specific fuel consumption taken as 0.3 l kWh −1 .…”
Section: Methodsmentioning
confidence: 99%
“…where x is the exogenous variable matrix [30], h is the endogenous variable matrix [30], B is the structural coefficient matrix that represents the influence between the constituent factors of the endogenous variable matrix h, Γ is the structural coefficient matrix [31], which represents the influence of the exogenous variable matrix x on the endogenous variable matrix h [31], and z is the residual matrix which represents the unexplained part [31].…”
Section: Path Analysismentioning
confidence: 99%
“…For example, Paudel et al [17] found that the adoption of agricultural machinery could improve rice productivity by 1110 kg/ha. Thus, agricultural mechanization is the key method for developing countries to realize agricultural modernization [18,19]. However, farmers often do not adopt it or take a long time to start adopting it [20].…”
Section: Introductionmentioning
confidence: 99%